Revealing Pt-seed-induced structural effects to tribological/electrical/thermoelectric modulations in two-dimensional PtSe2 using scanning probe microscopy. (January 2022) - Kim, Jong Hun; Youn, Seonhye; Go, Tae Won; Kim, Jeongmin; Yoo, Changhyeon; Shawkat, Mashiyat Sumaiya; Han, Sang Sub; Jeon, Seong-jae; Jung, Yeonwoong; Park, Jeong Young; Lee, Wooyoung
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDCs) provide an opportunity to investigate diverse scientific phenomena at an atomic level and have effective technological potential. In recent times, unlike conventional TMDCs, platinum diselenide (PtSe2 ) has garnered considerable attention owing to its i) fascinating electrical and optical features coupled with mechanical strain and ii) scalable synthesis method. However, its local electrical/tribological/mechanical properties are yet to be examined in detail. In this study, we prepared two different types of PtSe2 layers by controlling the thickness of the Pt-seed film: i) one with horizontal alignments, which are made from ultrathin Pt films and ii) one with vertical and horizontal alignments, which are made from a relatively thick Pt film. Then, the local tribological, mechanical, and electrical properties of PtSe2 were evaluated mainly with scanning probe microscopy (SPM). The local friction study unveiled the marked friction variation depending on the layer directions. An additional study on the local mechanical property indicated that the apparent modulus difference between the two growth directions can lead to dissimilar friction behaviors. Furthermore, local current probing using SPM showed that PtSe2 with both layer directions provides ohmic features to both directions, although the magnitude of conductance along the horizontal direction is 100 times smaller than that along the vertical one. On the contrary, PtSe2 with only in-plane alignments is configured with multiple horizontal PtSe2 layers, densely stitching themselves together one after another with a very narrow trench region at their boundary. Surprisingly, a local current–voltage spectroscopy analysis showed a small current gap on the bridged trench region, in contrast to the ohmic behavior of the grain interior. This indicates that the local metal-to-semiconductor transition is available, owing to thin PtSe2 layers in the trench regions. The following study at macroscale showed how the overall electrical and thermoelectric properties of PtSe2 can be influenced by local structures triggered by the variation in Pt-seed thickness. The results not only provide a new insight on better understanding the intrinsic features of 2D PtSe2, but also offer important characterization guidance on tailoring their functionalities. Graphical Abstract: ga1 Highlights: With increasing 2D layer thickness, the layer orientation of 2D PtSe2 transits from horizontal-to-vertical direction. Friction, mechanical, and electrical properties were clearly observed at the nanoscale by SPM. The friction of 2D PtSe2 with different growth direction configurations exhibited distinctively different behaviors, owing to the modulus-induced contact area variation. PtSe2 only with the horizontal alignments exhibited the semiconducting behavior in the intergranular region in contrast to the metallic grain interior. The electrical and thermoelectric properties of PtSe2 at the device scale can be influenced by local structures triggered by the variation in Pt-seed thickness.